2016
DOI: 10.3892/or.2016.5163
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-124 inhibits cell proliferation and migration by regulating SNAI2 in breast cancer

Abstract: Abstract. MicroRNA (miRNA) is a type of endogenous non-coding RNA implicated in various cellular processes. Studies have shown that miR-124 is involved in the malignant progression of cancer, but little is known concerning its potential role in breast cancer. Therefore, the purpose of this study was to conduct a functional analysis of miR-124 in breast cancer, and to identify its target genes in this disease. To this end, we used quantitative real-time PCR to examine the expression level of miR-124 in breast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 52 publications
2
17
0
Order By: Relevance
“…SNAI2 was a member of SNAIL family of EMT associated transcription factors and accepted as an oncogene. Abnormally high expression of SNAI2 has been found in various cancers, including breast cancer [30], colorectal cancer [31] and melanoma [32]. Interestingly, Zhao et al first discovered that SNAI2 could as a tumor suppressor by repressing multidrug resistance via decreasing ABC transporter genes in hepatocellular carcinoma cells [33].…”
Section: Discussionmentioning
confidence: 99%
“…SNAI2 was a member of SNAIL family of EMT associated transcription factors and accepted as an oncogene. Abnormally high expression of SNAI2 has been found in various cancers, including breast cancer [30], colorectal cancer [31] and melanoma [32]. Interestingly, Zhao et al first discovered that SNAI2 could as a tumor suppressor by repressing multidrug resistance via decreasing ABC transporter genes in hepatocellular carcinoma cells [33].…”
Section: Discussionmentioning
confidence: 99%
“…Cell migration is an important determinant of the efficiency of MSC transplant therapy [ 41 ]. Previously, there are study reported that overexpression of miR124 suppresses the migration of several cell lineages, including glioma [ 42–44 ], bladder cancer cells [ 45 , 46 ], osteosarcoma cells [ 47 , 48 ], breast cancer cells [ 49 , 50 ], and lung cancer cells [ 51 ]. It is also reported that miR124 down-regulates Wnt/β-catenin signaling via targeting the frizzled-4 (FZD4) and low-density lipoprotein receptor-related protein 6 (LRP6) and thus suppresses the chemotactic migration of MSCs toward hepatocyte growth factor (HGF), a chemoattractant factor [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among them are miR-30a [70], miR-122 [95], miR-182 [115], and miR-203 [115] and miR-204 [116]. SLUG is targeted in in oral squamous cell carcinoma by miR-204 [116]; glioblastoma by miR-203 [117]; in lung cancer by miR-1 [118]; in breast cancer by miR-124 [119,120], miR-30a [70], miR-497 [121], miR-1271 [122], and miR-203 [123,124]; in gastric cancer by miR-33a [125]; in lung cancer by miR-218 [126]; in clear cell renal cell carcinoma by miR-1 [127]; in osteosarcoma by miR-124 [128]; and in gingival fibroblasts by miR-200b [129]. Similarly to SNAIL, miRNAs-SLUG action regulates EMT in cancer progression, as well as different processes, such as the modulation of cancer stem cells' activity.…”
Section: Regulation Of Slug Expression By Micrornasmentioning
confidence: 99%
“…Cancer/Cell Type References miR-1 lung cancer [118] miR-30a breast cancer [70] miR-33a gastric cancer [125] miR-124 breast cancer [119,120] osteosarcoma [128] glioma [130] miR-200b gingival fibroblasts [129] miR-203 glioblastoma [117] breast cancer [123,124] miR-204 oral squamous cell carcinoma [116] miR-218 lung cancer [126] miR-497 breast cancer [121] miR-630 dermal microvascular endothelial cells [131] miR-1271 breast cancer [122]…”
Section: Micrornamentioning
confidence: 99%